Accuracy of endoscopic ultrasonography in upper gastrointestinal submucosal lesions - Dilek OĞUZ; Levent FİLİK and Erkan PARLAK and Selçuk DİŞİBEYAZ and; ttin ÇİÇEK and Sabite KACAR and Gülden AYDOĞ and Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-